R&D Deal - The Star (2008)
Datuk Mustapa Mohamed witnessing the exchanging of documents between Padiberas Nasional Bhd director Datuk Azizan Ayob (left) and University Putra Malaysia vice-chancellor Prof.Datuk Dr. Nik Mustapha Raja Abdullah Yesterday.